Mining Crisis and National Strike,1925/26 - Miners Federation of GB conference, 20 May 1925 (page 3)
1925-05-20 "Mining Crisis and National Strike,1925/26 - Miners Federation of GB conference, 20 May 1925 (page 3)" [g0487003.jpg], 20 May 1925, Miners' Federation of Great Britain